Diseño de un estimulador para generar la succión en recién nacidos prematuros - Yika Tuesta, Alberto Stavros (2009)
This work raises a solution for the development of the sucking reflex in premature infants. This solution is based on a computer that uses a system of control of negative pressure applied directly in a pacifier common through a dock. In turn, this process is performed using a generator of waves that controls the frequency of suction as well as the kind of stimulation granted. The systems of stimulation of suction in preterm infants are presented as the solution, in the face of scarce stimulators of language, and the presence of latent problem. Currently, there are many researches [2] that have collaborated with the development process of the language, which would not only be measured patterns engines of non-nutritive sucking, but also produce a stimulator natural and harmless with the proper frequency response. The pacing system suction proposes stimulation based on control of a pneumatic motor and sensing constant on a variety of parameters, which provide an effective and natural exercise, for newborns in addition to cost reduction in the case of a treatment of short duration. Therefore, this thesis aims to design a stimulator system based on the generation of vacuum and inflated through a valve pneumatic, and sensing constant on a variety of parameters in order to stimulate the newborn premature to assist in the development of non-nutritive sucking, which directly affects their language . The main conclusion it should be mentioned that it is possible to obtain all the patterns engines of the suction non-nutritious to then use these in the construction of the signal generator of stimulation in the system that was developed in laboratory conditions. And it is important the contribution of this multidisciplinary work where unite two areas: neuroscience and electronics, resulting in initiating investigations in the field of the neurocognitive language disorder in children. [2]. FINAN, DS., BARLOW, SM., The actifier: a device for neurophysiological studies of orofacial control in human infants, Journal Speech Hear Research., vol. 39(4), pp. 833-8, Aug 1996.